2015
DOI: 10.1038/srep10322
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-Encapsulated Polymeric Micelles Suppress the Development of Colon Cancer In Vitro and In Vivo

Abstract: To develop injectable formulation and improve the stability of curcumin (Cur), Cur was encapsulated into monomethyl poly (ethylene glycol)-poly (ε-caprolactone)-poly (trimethylene carbonate) (MPEG-P(CL-co-TMC)) micelles through a single-step solid dispersion method. The obtained Cur micelles had a small particle size of 27.6 ± 0.7 nm with polydisperse index (PDI) of 0.11 ± 0.05, drug loading of 14.07 ± 0.94%, and encapsulation efficiency of 96.08 ± 3.23%. Both free Cur and Cur micelles efficiently suppressed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(90 citation statements)
references
References 42 publications
3
85
0
2
Order By: Relevance
“…Higher loading of Cur on GP was achieved as compared to other recently reported delivery cargos2425262728293031 (Supplementary Table S3). Even by utilizing GO, only 208 wt.% was obtained24 achieving only half of the loading capacity as compared to our current approach.…”
Section: Resultsmentioning
confidence: 75%
“…Higher loading of Cur on GP was achieved as compared to other recently reported delivery cargos2425262728293031 (Supplementary Table S3). Even by utilizing GO, only 208 wt.% was obtained24 achieving only half of the loading capacity as compared to our current approach.…”
Section: Resultsmentioning
confidence: 75%
“…Reports on cancer therapy in recent years have revealed that CM can cause apoptosis signals in various cancers. [23][24][25] As shown in Figure 5B and D, cells treated with CM-SF NPs showed a higher percentage of apoptosis (~23%) than those treated with 5-Fu (~16%). This indicates that CM-SF NPs had better apoptotic cell-induction potential than 5-Fu.…”
Section: Induction Of Cell Apoptosismentioning
confidence: 85%
“…Different kinds of delivery systems have been used to deliver curcumin to the brain and to glioblastoma in vivo [57][58][59]. Polymeric carriers have the potential to improve the stability and solubility of curcumin [60][61][62]. Our research group has previously reported the incorporation of curcumin into A2B star polymer micelles and effectiveness of this preparation in glioblastoma [63,64].…”
Section: Discussionmentioning
confidence: 99%